Nanomodified natural aluminum silicates in technology treatment of industrial waste and the production of building materials - Kuprienko, Peter; Lapovska, Svetlana; Kuprienko, Natalia (КНУБА, 2017)
The article presents the results of cleaning galvanic drains, etching solutions, waters contaminated water soluble fractions of petroleum products, including seawater. Conducted data testing of technology for recycling products of water treatment in the technology of production of ceramic bricks.
Keywords: galvanic drains; etching solutions; water soluble fractions of petroleum products.; 691.33:661.862